2011
DOI: 10.3139/217.2451
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Stochastic and Geometric Micro Structures – Aspects of Visual Appearance

Abstract: The surface quality of injection molded parts depends on the processing conditions, the cavity surface structure, the runner system, the used polymer and the part geometry. Different replication of the cavity surface structure to the molded part influences its surface function and visual appearance. A descriptive model of the replication process has been developed, taking into account the thickness of the frozen layer during injection. The expected dependencies were proven by systematic injection molding tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
4
21
0
1
Order By: Relevance
“…The lowest depth replication achieved in the vertical channels was probably due to the feature's higher aspect ratio (see Table 2). This coincides with studies suggested that better replication can be achieved with features having lower aspect ratios [11,12]. However, features aligned at 45° and which had lowest aspect ratios showed lower depth replication compared to the horizontal features.…”
Section: Aspect Ratio and Feature Orientationsupporting
confidence: 73%
See 1 more Smart Citation
“…The lowest depth replication achieved in the vertical channels was probably due to the feature's higher aspect ratio (see Table 2). This coincides with studies suggested that better replication can be achieved with features having lower aspect ratios [11,12]. However, features aligned at 45° and which had lowest aspect ratios showed lower depth replication compared to the horizontal features.…”
Section: Aspect Ratio and Feature Orientationsupporting
confidence: 73%
“…A study showed that vertical channels parallel to the melt flow direction in a dog-bone sample gave higher filling compared to horizontal channels which are perpendicular to the melt direction [6]. The better filling in the horizontal channels in this present study indicated that sample shape could affect the filling of features with a particular orientation [11].…”
Section: Aspect Ratio and Feature Orientationmentioning
confidence: 60%
“…affected by mold temperature both in longitudinal to (the third in ranking order) and transversal to (the second in ranking order) the flow direction. By considering semicrystalline (POM [106,111,112], HDPE and PP [105], HCPP and PC [113,114], PP and PA [111] or PA mixed with 316L [115]), amorphous polymers (PMMA [105,113,116], PS [105,113], COC [117], ABS [118]) or ceramic feedstock (Zr [119]), results identified the mold temperature as a critical parameter affecting shrinkage. Also, authors [11,112,120] determined that by increasing this parameter, led to an increased shrinkage.…”
Section: Processing Parameter Influencesmentioning
confidence: 99%
“…This parameter affected shrinkage in semicrystalline (POM [11], HDPE [105], HCPP [114], PC [113,114], PP [105]) amorphous (PMMA [105,110,113], PS [105,113]) or cyclic olefin polymers [117].…”
Section: Processing Parameter Influencesmentioning
confidence: 99%
“…Wykorzystuje się ją w wielu gałęziach przemysłu, począwszy od produkcji zabawek, artykułów gospodarstwa domowego, sprzętu elektronicznego i medycznego, a skończywszy na branży samochodowej, lotniczej i chemicznej. Technologia polega na wtryskiwaniu uplastycznionego tworzywa sztucznego do gniazda formy wtryskowej [6]. W ten sposób powstaje wypraska odwzorowująca kształt gniazda o specyficznych właściwościach fizycznych, zależnych od przebiegu procesu technologicznego [1].…”
unclassified